Cultural Values Revitalization: A Post-Conflict Peace Building Effort in Ambon City - Sunarimahingsih, Yulita Titik; Susanti, B. Tyas; Dewi, Y. Trihoni Nalesti (Soegijapranata Catholic University, 2022)
Ambon has experienced a social disaster in the form of a conflict that occurred in 1999-2004. Many attempts were made to overcome it. Basically, the Ambonese people have unique traditions and cultural symbols that can be a means of uniting them, but small emotional flareups still appear which cause further friction and conflict, therefore revitalizing the local cultural values is important. The revitalization of Ambonese cultural values and traditional symbols is important. Currently, the gap in communication and understanding of noble values, local wisdom, and the meaning of cultural symbols is the main obstacle in efforts to use it for reconciliation. This research reports the aim of finding a strategy for revitalizing cultural values and cultural symbols in Ambon, as one way to promote sustainable peace and rebuild Ambon's identity as a city that is full of local philosophy and cultural wisdom. The method used is a qualitative method with post-disaster management analysis. The research finds that a revitalization process strategy for reconciliation can be done by means of (1) Building integration of local wisdom and culture in public space, and (2) internalizing the local values and the marking of cultural symbols.